A Causal Relationship between Energy Consumption, Energy Prices and Economic Growth in Africa - Sharmin, Farzana; Khan, Mohammed Robayet (International Journal of Energy Economics and Policy, 2016)
This paper examines the causal relationships between energy consumption, income and energy prices for the African countries using Johansen’s maximum-likelihood test of cointegration and Error-Correction Model (ECM). To have a reliable estimate, only countries having data availability for a minimum period of 25 years were considered. This requirement reduces the sample size to 26 countries only. Out of these, a long run cointegrating relationship was found for a total of six countries, which was then subsequently analyzed to confer on the direction of causality. Out of the reported five countries, we found the existence of bidirectional Granger causality for Ethiopia, Morocco and Mozambique. The result for Angola suggests unidirectional Granger causality running from income to energy consumption while no Granger causality for the case of Tanzania. Findings suggest that countries regardless of their level of income and development should direct their energy conservation policies on the basis of the energy-output causality relation. Keywords: energy; Johansen’s maximum likelihood test of cointegration; Error Correction Model. JEL Classifications: C22; Q43; Q48